SAT0053 Identification of novel drugs with senolytic activity as osteoarthritis therapeutics. (12th June 2018) - Nogueira-Recalde, U.; Blanco, F.J.; Loza, M.I.; Grassi, D.; Robbins, P.; Dominguez, E.; Carames, B.
Abstract : Background: Disease-modifying treatments for Osteoarthritis (OA) are not available. Aging-related features such as failure of cellular homeostasis mechanisms, including autophagy, cause extracellular matrix damage, chondrocyte senescence and death, which leads to articular cartilage degeneration as well as loss of joint function. Objectives: The objective of this study was to identify senolytics and activators of autophagy by cell-based imaging of approved drugs in human chondrocytes. Methods: To induce cellular senescence and reduced autophagy, High Content Screening system. Validation assays with readouts for senescence, autophagic flux, inflammation and apoptosis in primary human chondrocytes were performed. The anabolic effect on human cartilage and chondrocytes was evaluated by Safranin O staining and Nitric oxide production. To define the effects on senescence (senomorphic or senolytic), TC28a2 chondrocytes and human lung fibroblasts (IMR90) were employed. Senescence was induced in TC28a2 and IMR90 by treatment with IL-6 (20 ng/ml) for 72 hours and Etoposide (20 µM) for 48 hours, respectively, and treated with serial dilutions of identified compounds. The number of senescence cells and the number of total cells were determined with Cell Analyzer 6000 Confocal Imaging System. Navitoclax (2, 5 µM) and Rapamycin (10 µM) were employed as reference controls for senolytic and senomorphic effects, respectively. Results: Our primary screen yielded 279 senotherapeutic compounds. The effects of hits at inducing the autophagic flux were evaluated. 37 compounds with both senotherapeutic and pro-autophagy effects were selected. An approved drug with a defined molecular mechanism of action was selected for further validation. The compound reduced senescence (p<0.001) and increased autophagic flux (p<0.0001). Furthermore, we found that it protects against defective autophagy and inflammation in response to IL-6 and IL-1b. This protective effect was confirmed in human cartilage explants by a reduction of proteoglycans loss (p<0.05) and in primary human chondrocytes by a reduction of NO production and chondrocyte death by apoptosis (p<0.0001). Moreover, a significant senolytic effect of the selected compound was observed in both chondrocytes and fibroblasts (p<0.05). This effect was also observed for structurally different compounds sharing the same mechanism of action, suggesting that pharmacological modulation of this mechanism may provide therapeutic benefits in OA. Conclusions: Our imaging screening methodology provides a unique opportunity to identify drugs and mechanisms to prevent cartilage pathology. Autophagy activation and disruption of senescence may provide benefits for delaying cartilage degeneration. Acknowledgements: Disclosure of Interest: None declared